Gender-based violence in South Africa: A narrative reflection - Buqa, Wonke (HTS teologiese studies, 2022)
The pervasiveness of gender-based violence (GBV) against women and children constitutes the most severe expression of discrimination and dehumanisation of women and children in South Africa. Even before the coronavirus disease 2019 (COVID-19) pandemic came, domestic violence was already one of the greatest human rights violations. Women for centuries suffered different forms of violation and continue to struggle in subtle forms in the 21st century. This article investigates the sociocultural theories, narrative reflections and COVID-19 pandemic challenges associated with the prevalence of GBV in South Africa. The article argues that patriarchal culture, religion, gender norms, lockdown and violence in South Africa perpetuate gender-based abuse. Therefore, the article unfolds this research through a literature review and narrative approach which is used to allow the co-researchers to share their stories. The article embarks on sociocultural experiences, the scourge of GBV in South Africa, the impact of COVID-19 pandemic, qualitative interviews and theological reflections and concludes by suggesting future possibilities to fight GBV.Contribution: This article contributes to an understanding that abafazi nabantwana baphefumla ngenxeba [women and children are breathing through the wound] amid the global COVID-19 pandemic. It discusses the prevalence of GBV, the intersection of religious cultural effects, social sciences, gender inequality and the continued oppression of women and children.